Addressing geographical variation in the progression of non-communicable diseases in Peru: the CRONICAS cohort study protocol. Issue 1 (11th January 2012) - Miranda, J Jaime; Bernabe-Ortiz, Antonio; Smeeth, Liam; Gilman, Robert H; Checkley, William; ,
Abstract : Background: The rise in non-communicable diseases in developing countries has gained increased attention. Given that around 80% of deaths related to non-communicable diseases occur in low- and middle-income countries, there is a need for local knowledge to address such problems. Longitudinal studies can provide valuable information about disease burden of non-communicable diseases in Latin America to inform both public health and clinical settings. Methods: The CRONICAS cohort is a longitudinal study performed in three Peruvian settings that differ by degree of urbanisation, level of outdoor and indoor pollution and altitude. The author sought to enrol an age- and sex-stratified random sample of 1000 participants at each site. Study procedures include questionnaires on socio-demographics and well-known risk factors for cardiopulmonary disease, blood draw, anthropometry and body composition, blood pressure and spirometry before and after bronchodilators. All participants will be visited at baseline, at 20 and 40 months. A random sample of 100 households at each site will be assessed for 24 h particulate matter concentration. Primary outcomes include prevalence of risk factors for cardiopulmonary diseases, changes in blood pressure and blood glucose over time and decline in lung function. Discussion: There is an urgent need to characterise the prevalence and burden of non-communicable diseases in low- and middle-income countries. Peru is a middle-income country currently undergoing a rapid epidemiological transition. This longitudinal study will provide valuable information on cardiopulmonary outcomes in three different settings and will provide a platform to address potential interventions that are locally relevant or applicable to other similar settings in Latin America.